2021
DOI: 10.3390/genes12071023
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Zebrafish MicroRNA-145 and Its Role during Neural Crest Cell Development

Abstract: The neural crest is a multipotent cell population that develops from the dorsal neural fold of vertebrate embryos in order to migrate extensively and differentiate into a variety of tissues. A number of gene regulatory networks coordinating neural crest cell specification and differentiation have been extensively studied to date. Although several publications suggest a common role for microRNA-145 (miR-145) in molecular reprogramming for cell cycle regulation and/or cellular differentiation, little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In order to determine if the microinjected PSN miR145 or the free miR145 were able to modify sox9b and/or gata6 expression, a RT-qPCR was performed 3 days later (72 hpf). In accordance with previous observations ( Zeng et al, 2009 ; Steeman et al, 2021 ), miR145 increase led to a significant decrease in sox9b ( p value 0,0347) and gata6 ( p value 0,0364) expression but only when associated in PSN ( Figure 2 ), and not when microinjected alone, in 72 hpf zebrafish embryos. Similarly, neither free miR control nor PSN alone nor PSN/miR control were able to modify their expression.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In order to determine if the microinjected PSN miR145 or the free miR145 were able to modify sox9b and/or gata6 expression, a RT-qPCR was performed 3 days later (72 hpf). In accordance with previous observations ( Zeng et al, 2009 ; Steeman et al, 2021 ), miR145 increase led to a significant decrease in sox9b ( p value 0,0347) and gata6 ( p value 0,0364) expression but only when associated in PSN ( Figure 2 ), and not when microinjected alone, in 72 hpf zebrafish embryos. Similarly, neither free miR control nor PSN alone nor PSN/miR control were able to modify their expression.…”
Section: Resultssupporting
confidence: 93%
“…With the aim of studying the correct release of the associated NAs inside the cells, miR 145 was chosen due to its effect on gene expression in the zebrafish embryo. This miR is known to downregulate sox9b and gata6 genes when overexpressed in zebrafish ( Zeng et al, 2009 ; Steeman et al, 2021 ). Embryos of 0 hpf, one-cell stage, were microinjected with PSN associated and non-associated with miR (Control and 145), and with free miR (Control and 145).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both miRNA biogenesis and miRNA‐mediated repression have reiterative roles throughout neural crest development, from induction and cell survival through differentiation, across multiple organisms (Antonaci & Wheeler, 2022; Chapnik et al, 2012; Copeland & Simoes‐Costa, 2020; Keuls et al, 2023; Steeman et al, 2021; Ward et al, 2018). In particular, a handful of miRNAs have been implicated in the delamination and migratory phases of neural crest, including miR‐34a , miR‐203 , and let‐7 , the regulatory roles of which we briefly discuss below (for further reading and additional reviews on this topic, see Antonaci & Wheeler, 2022; Hardy et al, 2017).…”
Section: Emt Regulation At the Rna Levelmentioning
confidence: 99%
“…For example, Steeman and colleagues have shown that the highly conserved miR-145, which is transcribed together with miR-143, plays a role during craniofacial development in zebrafish. They speculated that this might be caused by a direct interaction between miR-145 and Sox9b [ 43 ]. Zhao and colleagues, also working in zebrafish, have shown that miR-1 plays a role in NC development, as its knock-down produces defects during craniofacial, heart, melanocyte and iridophore development [ 44 ].…”
Section: The Role Of Mirnas In Nc Developmentmentioning
confidence: 99%